A single-center study on impact of psychological intervention to acclimatize medical staffs who are serving COVID-19 disease patients, to continue hospital activities without any disruption - Dalal, Dhaval; Thiyagarajan, Kamalpriya; Nipane, Humeshwari; Gawali, Vijaykumar (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 has brought psychological disorders that affect health care workers and the general public. Hence it is important to have necessary counselling to address the psychological, social aspects of the pandemic to ensure psychological well-being of especially Health-care Workers and preserve their innate and acquired immunity. Methods: The study was planned as single centre retrospective study and conducted between April and June 2020 at dedicated COVID-19 hospital in India. Front-line HCWs more than 18 years, of any gender working in COVID-19 hospital and willing to participate for the study were enrolled in the study. Study included two questionnaires, generalized anxiety disorder scale, and socio-demographics and COVID-19 related awareness questionnaire. Measurements were taken pre and post the psychological counselling intervention. Results: As per generalized anxiety disorder (GAD) scale people suffering from moderate anxiety disorder dropped from 19% (pre counselling) to 5% (post counselling) and severe cases dropped from 14% (pre counseling) to 2% (post counseling), there was statistically significant difference observed due to psychological intervention in GAD scale (Chi square test-10.794, p value=3.67E-27). Socio demographics and COVID-19 related awareness questionnaire results were statistically significant (Chi square test-11.945, p value=6.91E-33). Conclusions: Counselling interventions based on scientific data offered in groups by investigator with an accurate knowledge of the COVID-19 and its manifestation increased the confidence of health care workers (HCWs) and reduced anxiety level. This was translated into the full availability of HCWs on the clinical study site, although medical services were disrupted while other hospitals were starving due to lack of staff.